Determination of symmetry plane on human brain CT images - Grigaitis, Darius; Meilūnas, Mečys (Lietuvos matematikos rinkinys, 2023)
A method of automatic detection of human brain symmetry plain in computed tomography (CT) images is  described. An algorithm consists of four steps: region of interest, symmetry curve detection, symmetry axis evaluation and calculation of symmetry plane. Symmetry plane are calculated using vertex slices of human brain CT images. There are approximately 40 which has symmetry curve ``  `  Falx cerebri'' property. In the first, using this feature symmetry axis in slice detected. In second, coordinates of detected symmetry axis and least square method are used to calculate symmetry plane. In others images where symmetry property is not available symmetry axis is projection of calculated plane.
Keywords: symmetry plane; symmetry curve; Falx cerebri; least square